Automation Capabilities for the Logistics Service of Jobshop Production System - Ferenczi, Balázs; Németh, Péter (International Journal of Engineering and Management Sciences, 2020)
One of the most important subsystems of manufacturing is the logistics system for transporting materials between technological phase. It is integrated depending on the production structure. The special feature of highly flexible workshop system production is that the material handling system is typically separate and the movement needs occur independently of each other, so the flexibility of the material handling system is required to achieve the expected production goal. In practice, therefore, the organization and execution of material handling is to a considerable extent dependent on the human factor. The purpose of this research is to explore the potential for automation of material handling activities in this particular production environment.